“But We Just Need Money”: (Im)Possibilities of Co‐Producing Knowledge With Those in Vulnerable Situations - Jane Freedman; Tamaryn L. Crankshaw; Yasmin Rajah; Victoria Marcia Mutambara (Social Inclusion)
This article is based on the experience of carrying out research with young refugee women in Durban, South Africa. We reflect on the possibilities of co‐producing knowledge in a situation of widely asymmetrical power relations where the young women with whom we were interacting were located in situations of economic, legal, and social vulnerability, and when their major concern was to find money for basic survival. The premise behind our research was to produce data and knowledge that could be used to improve services for these young refugee women and to lobby for change in policies that would also improve their life situations. Our article reflects on this ambition and the possibilities of co‐producing knowledge that could improve these young women’s lives, our interactions with the young refugee women, and with the CSO that offers them support and with whom we partnered to organize our data collection. We also analyse the different positionalities of various members of the research team and how these impacted the data collection and knowledge production processes. The article aims to provide a critical assessment of the ways in which knowledge production may or may not be a liberatory practice and the conditions within which true co‐production of knowledge is possible. We ask whether it is, in fact, possible to co‐produce knowledge when working with people in vulnerable situations such as the women refugees in our project. As academics, how may we learn from our failures to try and move forward with more truly inclusive and equitable research that challenges epistemic oppression?